2014
DOI: 10.1002/lt.23819
|View full text |Cite
|
Sign up to set email alerts
|

Single-center experience and long-term outcomes of duct-to-duct biliary reconstruction in infantile living donor liver transplantation

Abstract: The indications for duct-to-duct (DD) biliary reconstruction in living donor liver transplantation (LDLT) for small children are still controversial. In this study, the feasibility of DD biliary reconstruction versus Roux-en-Y (RY) biliary reconstruction was investigated in terms of long-term outcomes. Fifty-six children who consecutively underwent LDLT with a weight less than or equal to 10.0 kg were enrolled. Biliary reconstruction was performed in a DD fashion for 20 patients and in an RY fashion for 36 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…The incidence of biliary stricture after pediatric LT ranges from 4.5% to 14.9% and from 8.9% to 16.7% in smaller infants, which is comparable to the incidence of 5.4% reported in the present series. Similarly, reported biliary leak ranges from 0% to 21.4% in pediatric LT, and in our study, the incidence of biliary leak in smaller infants was 2.7%. Some studies have suggested that the incidence of biliary complications in smaller infants is similar to that of older children .…”
Section: Discussionsupporting
confidence: 85%
“…The incidence of biliary stricture after pediatric LT ranges from 4.5% to 14.9% and from 8.9% to 16.7% in smaller infants, which is comparable to the incidence of 5.4% reported in the present series. Similarly, reported biliary leak ranges from 0% to 21.4% in pediatric LT, and in our study, the incidence of biliary leak in smaller infants was 2.7%. Some studies have suggested that the incidence of biliary complications in smaller infants is similar to that of older children .…”
Section: Discussionsupporting
confidence: 85%
“…However, biliary complications caused by these reasons do not commonly occur because Roux‐en‐Y hepaticojejunostomy remains the standard treatment of choice for pediatric LDLT, which may be less susceptible to bile duct deformity. A recent study by Yamamoto et al . reported two children who developed deformity of the extrahepatic duct 4 and 9 years after LDLT, respectively, but no clinical signs associated with the deformity were observed.…”
Section: Discussionmentioning
confidence: 96%
“…3 For pediatric LDLT, many researches have focused on the technical improvement to prevent adverse events related to regeneration of the partial graft and the growth of children. 5,6,9,10 However, biliary complications caused by these reasons do not commonly occur because Roux-en-Y hepaticojejunostomy remains the standard treatment of choice for pediatric LDLT, which may be less susceptible to bile duct deformity. A recent study by Yamamoto etal.…”
Section: Discussionmentioning
confidence: 99%
“…With DD reconstruction becoming increasingly common in adult liver transplantations, fresh data are beginning to accumulate about its implementations in pediatric patients. (1,3) A majority of these data covers living donor liver transplantation (LDLT) patients and to our best knowledge, there is no report on the outcomes of DD biliary reconstruction for pediatric patients in the setting of SLT.…”
Section: Discussionmentioning
confidence: 99%